Enhancing table tennis performance and physical fitness through digital technology: a quasi-experimental study based on the TPACK framework - Dongfang Xie; Baibing Chen; Baibing Chen; Hong Li; Qiwei Huang (Frontiers in Sports and Active Living)
Educational digitization has made integrating digital technology into physical education a pivotal strategy for transforming pedagogy. Guided by the Technological Pedagogical Content Knowledge (TPACK) framework, this study addresses two challenges in Chinese university physical education: the lack of evidence-based research on technology integration, and the decline in student physical fitness alongside the waning effectiveness of traditional table tennis instruction. We propose a “3 + 1” digital teaching model integrating multimedia, virtual reality (VR), augmented reality (AR), and artificial intelligence (AI) into a cohesive curriculum, aiming to enhance students' physical fitness and table tennis proficiency. We employed a sequential explanatory mixed-methods design. Initially, a survey of 1,200 undergraduates enrolled in elective table tennis courses across 10 universities in Guangxi, China, assessed instructional needs. Subsequently, a 16-week quasi-experimental study involving 270 students from Guangxi University (experimental group, n = 135; control group, n = 135) was conducted. While the control group maintained traditional instruction, the experimental group utilized the “3 + 1” digital curriculum. Pre- and post-intervention evaluations included quantitative assessments of table tennis skills and cardiovascular endurance, complemented by qualitative data from observations and student interviews. Quantitative results demonstrated significant improvements in the experimental group, with a 15% greater improvement in table tennis skills (p < 0.01) and a 10% higher increase in cardiovascular endurance (p < 0.05) compared to the control group. Qualitative analysis highlighted the experimental group's increased acceptance of technology, heightened engagement, deeper immersion, and enhanced motivation and interest in table tennis practice. These results confirm that the digitally empowered teaching model effectively enhances university students' physical fitness and athletic performance. Integrating TPACK-based pedagogical strategies with advanced digital tools, this approach offers substantial theoretical and practical implications for the reform of university physical education. Additionally, the study aligns with the United Nations Sustainable Development Goal 4 (Quality Education) by promoting innovative sports pedagogy. Future research should broaden the participant diversity and explore digital technology applications across additional sports disciplines to facilitate comprehensive digitization in physical education.